2022
DOI: 10.1101/2022.10.24.511199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morpho-electric and transcriptomic divergence of the layer 1 interneuron repertoire in human versus mouse neocortex

Abstract: Neocortical layer 1 (L1) is a site of convergence between pyramidal neuron dendrites and feedback axons where local inhibitory signaling can profoundly shape cortical processing. Evolutionary expansion of human neocortex is marked by distinctive pyramidal neuron types with extensive branching in L1, but whether L1 interneurons are similarly diverse is underexplored. Using patch-seq recordings from human neurosurgically resected tissues, we identified four transcriptomically defined subclasses, unique subtypes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 85 publications
3
19
0
2
Order By: Relevance
“…In contrast, we identified a notable gene expression signature in a subset of our dataset corresponding to a module of microglia related genes. Surprisingly, this identical signature was observed for both neurons recorded in acute and cultured slices (but more pronounced in culture) and has been similarly observed in other human and mouse acute brain slice Patch-seq datasets ( 1517 , 35 , 36 ). Further work is warranted to understand the cause and consequences of this gene expression signature in brain slice experiments.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In contrast, we identified a notable gene expression signature in a subset of our dataset corresponding to a module of microglia related genes. Surprisingly, this identical signature was observed for both neurons recorded in acute and cultured slices (but more pronounced in culture) and has been similarly observed in other human and mouse acute brain slice Patch-seq datasets ( 1517 , 35 , 36 ). Further work is warranted to understand the cause and consequences of this gene expression signature in brain slice experiments.…”
Section: Discussionsupporting
confidence: 81%
“…Human samples were obtained from neurosurgically resected neocortical tissues and processed with standardized protocols across three experimental sites in the U.S., Netherlands and Hungary ( 14 , 15 , 18 , 35 ); most samples originated from the temporal and frontal lobes, along with smaller fractions in parietal, occipital and cingulate areas (Data S1). Human Patch-seq neurons were mapped to a middle temporal gyrus (MTG) single nucleus transcriptomics-based reference taxonomy ( 1 ) and assigned to a transcriptomic subclass and type using a “tree mapping” classifier (see Methods) ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These analyses provide a new map for the field to understand organizational principles and place a cellular lens on thinking about cortical functional variation as variation in the proportions and properties of the component cell types that define the input-output properties of those areas. Recent studies have shown that morphological and anatomical characteristics are correlated with transcriptomic identity and gradient properties ( 16 , 24 , 66 ), indicating that the transcriptomic maps are also highly predictive for cell phenotype variation. Challenges for the future will be to map the entire human neocortex, understand graded features versus discrete boundaries, and directly measure the relationship between transcriptomically defined cell types, cellular phenotypes and functional architecture.…”
Section: Discussionmentioning
confidence: 99%